PENGARUH PEMBERIAN MEDIA TIKTOK KOMBINASI DEMONSTRASI TERHADAP TINGKAT PENGETAHUAN TENTANG CA PAYUDARA, SADARI DAN KETERAMPILAN PRAKTIK SADARI PADA REMAJA - Meliani Meliani; Sri Winarsih; Siti Chunaeni (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2025)
Breast cancer is cells that grow abnormally and uncontrollably in breast tissue and can metastasize to other organs around the breast. One of the early detections of breast cancer is breast self-examination (BSE), which is a self-examination by observing and examining the breasts to find out whether there are lumps or abnormalities that occur early on. The aim of this research is to determine the effect of providing TikTok combined demonstration media on the level of knowledge about breast Ca, BSE and BSE practice skills in adolescents. This research was conducted at SMP N 1 Kaliangkrik, Magelang Regency. The respondents in this study were 39 young women from SMP N 1 Kaliangkrik. This research uses a pre-experimental method with a one group pretest posttest design. The sampling technique used was total sampling and analyzed using the Wilcoxon test. The results of the research show that there is an effect of giving TikTok combined demonstration media on the level of knowledge about breast Ca, BSE and BSE practice skills in adolescents with the results of the Wilcoxon statistical test of Z calculating knowledge of -5.383 and skills of -5.452 with a p-value of 0.000 < 0.05.